Using AUSGeoid2020 and its error grids in surveying computations. Issue 3 (2nd September 2019) - Featherstone, W. E.; McCubbine, J. C.; Claessens, S. J.; Belton, D.; Brown, N. J.
ABSTRACT: We present summarised formulas and worked examples for the propagation of geoid and vertical deflection errors through some common geodetic surveying computations, as well as a demonstration of their effects on least squares adjustments of small simulated geodetic networks. We also present location-specific uncertainties for the vertical deflections derived from the horizontal gradients of the AGQG2017 gravimetric-only quasigeoid model, upon which AUSGeoid2020 is based.